Automation of Aquaponic Choy Sum and Nile Tilapia Using Arduino Microcontroller - Arif Widi Atmaja; Daniel Rudiaman Sijabat; Febry Eka Purwiantono (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2021)
This study aims to build an aquaponics automation tool to simplify the control of fish and vegetable cultivation. The objects that were taken in this study were nile tilapia and choy sum. In this study, testing was carried out in an aquarium and hydroponic pipe to control nutrition, water turbidity, light, pH, feed, and temperature. The main tools used to build this automation include Arduino ESP-32, GY-302 Ambient Light Intensity Sensor, DFRobot Gravity Analog pH Sensor, DS18B20 temperature sensor, 3-6V DC R140 DC motor, Relay Module6 Chanel 12V, RTC Module. DS130 and SR04 Ultrasonic Sensor. After the system testing process, it can be concluded that this tool can support the process of cultivating nile tilapia and choy sum properly and make it easier for farmers to monitor aquaponics.